Antiobesity effect of Gynostemma pentaphyllum extract (actiponin): A randomized, double‐blind, placebo‐controlled trial. (5th September 2013) - Park, Soo‐Hyun; Huh, Tae‐Lin; Kim, Sun‐Young; Oh, Mi‐Ra; Tirupathi Pichiah, P.B.; Chae, Soo‐Wan; Cha, Youn‐Soo
<x xml:space="preserve">Abstract</x> Objective The effects of actiponin was investigated, a heat‐processed Gynostemma pentaphyllum extract, on body weight, fat loss, and metabolic markers of Korean participants in a 12‐week, randomized, double‐blind, placebo‐controlled clinical trial. Design and Methods Obese participants (BMI ≥ 25 kg m−2 and WHR ≥ 0.90 for male or WHR ≥ 0.85 for female) who had not been diagnosed with any disease and met the inclusion criteria were recruited for this study. The 80 subjects were randomly divided into actiponin (n = 40, 450 mg day−1) and placebo (n = 40) groups. Outcomes included measurement of efficacy (abdominal fat distribution, anthropometric parameters, and blood lipid profiles) and safety (adverse events, laboratory test results, electrocardiogram data, and vital signs). Results During 12‐week of actiponin supplementation, total abdominal fat area, body weight, body fat mass, percent body fat, and BMI were significantly decreased (P = 0.044, P < 0.05, P < 0.0001, P < 0.0001, and P < 0.05, respectively) in the actiponin group compared to the placebo group. No clinically significant changes in any safety parameter were observed. Conclusion Our study revealed that actiponin is a potent antiobesity reagent that does not produce any significant adverse effects. These results suggest that actiponin supplementation may be effective for treating obese individuals.